Peran Pola Asuh Orangtua Dalam Menanamkan Disiplin Pada Anak - Rohmah, Lailatu (ACIECE, 2016)
Parenting model played an influential role in cultivating discipline character for children. How the parent brought up their children at home would influence children’s character, including discipline. This conceptual paper explores the types of parenting that influence children’s character. There are four types of parenting, they are democratic, authoritarian, permissive, and negligance. From those types of parenting, the democratic has been proven to be more successfully in cultivating permanent discipline in child. The analysis showed that the democratic type of parenting has brought about children with the character of independency, good self control, have good relationship with their friends, able to deal with stress, have good interest to new things, discipline in conducting the rule agreed upon with their parent, and able to cooperate with others.